Malignant neoplasms of the oral cavity and oropharynx treated in Brazil: what do hospital cancer records reveal? - Sheilla de Oliveira Faria; Murilo César do Nascimento; Marco Aurélio Vamondes Kulcsar (Brazilian Journal of Otorhinolaryngology, 2022)
Introduction: Head and neck cancer has an impact on the global burden of diseases, representing an important cause of morbidity and mortality in Brazil, as well as worldwide. Objective: To learn and describe the clinical, epidemiological and care configuration provided to patients with cancer of the oral cavity and oropharynx recorded in Brazil, diagnosed from 2007 to 2016. Methods: This is a cross-sectional study, carried out using secondary hospital-based data, using the indirect documentation technique. Results: There were 52,799 hospital records of oral cavity cancer and 34,516 cases of oropharyngeal cancer in the assessed period. There was a predominance of male patients, aged 50–59 years, mostly Caucasians, and with a low level of schooling. Throughout the period there was a significant reduction in the positive history of alcohol and tobacco consumption, except for alcoholic beverages in oral cavity cancer. Most patients were diagnosed at an advanced stage of the disease (III or IV). Most patients with oral cavity cancer had no evidence of the disease on follow-up, while most patients with oropharyngeal cancer died. The first most frequent treatment offered to patients with oral cavity cancer was surgery, while for patients with oropharyngeal cancer it chemoradiotherapy predominated. Conclusion: Despite the fact that, in general, there was a reduction in the records of patient alcohol and tobacco consumption, the increase in the number of medical consultations, the predominantly late diagnosis and the patients’ low level of schooling indicate the need for health education, primary prevention and early diagnosis of cancer of the oral cavity and oropharynx.